1992
DOI: 10.1111/j.1749-6632.1992.tb27458.x
|View full text |Cite
|
Sign up to set email alerts
|

Thymic Involution in Aging Prospects for Correction

Abstract: The thymus produces several putative thymic hormones: thymosin alpha 1, thymulin, and thymopoietin, which have been reported to circulate and to act on both prothymocytes and mature T cells in the periphery, thus maintaining their commitment to the T cell system. These endocrine influences decline with age and are associated with "thymic menopause" and cellular immune senescence, which contribute to the development of diseases in the aged. Thymus endocrinology is characterized by the action of many hormones an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…Parallel with this, the production of self-hormones (thymulin, thymosin, thymopoietin, and THF) decreases and this could have an important role in the reduction of the lymphatic part. However, extrathymic actions of these hormones are also decreased, less participating in the complex endocrine regulation [154].…”
Section: Discussionmentioning
confidence: 99%
“…Parallel with this, the production of self-hormones (thymulin, thymosin, thymopoietin, and THF) decreases and this could have an important role in the reduction of the lymphatic part. However, extrathymic actions of these hormones are also decreased, less participating in the complex endocrine regulation [154].…”
Section: Discussionmentioning
confidence: 99%
“…Given the importance of immune function throughout life, this pattern of early expansion and subsequent regression has puzzled developmentalists and immunologists. The thymus in particular (labeled the "master gland" of the immune system for its critical role in T-cell development and function; Cotman et al, 1987) was identified by a number of investigators as a potential target for intervention in the aging process (Fabris et al, 1988;Hadden et al, 1993). Others suggested that regression protects against autoimmune reactivity later in life (Aronson, 1991), and minimizes energetic costs associated with this relatively expensive tissue (George and Ritter, 1996).…”
Section: Childhoodmentioning
confidence: 99%
“…The regression in the size, weight, and cellularity of the thymus is known as thymic involution (1)(2)(3)(4). Age-related thymic involution is considered an important factor in immune senescence (5)(6)(7).…”
mentioning
confidence: 99%